Assessment of infections rate due to community‐acquired Methicillin‐resistant Staphylococcus aureus and evaluation of risk factors in the paediatric population. (11th December 2020) - Galper, Ella; Bdolah‐Abram, Tali; Megged, Orli
Abstract: Aim: We aimed at assessing the frequency of Community‐acquired Methicillin‐resistant Staphylococcus aureus (CA‐MRSA) infections, identifying its risk factors and evaluating resistance patterns of Staphylococcus aureus to various antibiotics in order to recommend the optimal empirical treatment for suspected Staphylococcus aureus infections. Methods: We reviewed the medical records of children who were treated at Shaare Zedek medical centre, located in Jerusalem, Israel, over the years 2008–2019 and had a positive culture for Staphylococcus aureus . Patients with CA‐MRSA infections were compared with Methicillin‐susceptible Staphylococcus aureus (CA‐MSSA) infections. Results: In this study, 620 paediatric patients were included. The number of children in the CA‐MRSA study group was 124, while the MSSA control group consisted of 496 children. Risk factors for CA‐MRSA infections included young age (1–5 years), female sex, Arab ethnicity and residence in East Jerusalem. The incidence of CA‐MRSA increased over the past decade, with an average of 11.2%. An increase in MSSA resistance to clindamycin was noted while Trimethoprim‐Sulphamethoxazole resistance remained low. Conclusion: The incidence of CA‐MRSA in Jerusalem was rising, along with changes in resistance patterns of both MSSA and MRSA to various antibiotic agents. In order to optimise empirical treatment for suspected staphylococcal infection, continued monitoring of CA‐MRSA prevalence and resistance rates is essential.